Researching distance learning experiences using qualitative case study as a research method: Lessons learned - Dzakiria, Hisham (Penerbit Universiti Sains Malaysia, 2004)
Qualitative case study is hardly a research technique in its proper sense, but it is typical of most qualitative research to employ its usage in the research design. Hence, it merits some discussion.This paper considers some methodological issues of collecting qualitative data from distance learners at the Universiti Utara Malaysia (UUM).This paper begins with an overview of the study before describing the case study and the range of methods used. Then, it examines the merits and limitations of these research methods.Specifically, this paper discusses two methodological issues in qualitative case study: generalisation of research findings and integrity of research reports. Some concluding remarks are made about the appropriateness and effectiveness of the method used. The discussion in this paper is an attempt to highlight plausible major issues that researchers may encounter when the qualitative convention is adopted in the Malaysian educational research setting.